Sosialisasi Pendididikan Multikultural dalam Upaya Mewujudkan Transisi PAUD ke SD yang Menyenangkan - Maulida Nur; Muthia Sari; Alvina Lili Nurlita; Shofi Qutratu Aini; Vety Reza (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
When all parties work together, especially the role of elementary school teachers, a pleasant transition from ECCE to Elementry School is still their dream. This movement is expected not only to change policies. However, it can be achieved with the government's goal of making a pleasant transition for ECCE children entering elementary school. The goal of this initiative is to realize a pleasant transition from ECCE to Elementry School with multicultural education. The KKM 65 group did this work at Ambak Baya Elementary School and produced good results. Before the socialization, teachers tended to think that all early elementary school children should be able to read, write and write and were given the same treatment to each student without considering the readiness of each student, which would cause differences. After the socialization and final test, the KKM 65 group did this work. Teachers who are more